The effect of the patio on the indoor thermal performancein the colonial courtyard houses in the saharan climate. The case of Biskra in Algeria - Lebbal, Fatima-Zohra; Mazouz, Said (Journal of Applied Engineering Science & Technology; Vol 4 No 1 (2018), 2018)
A wide range of studies related to the evaluation of thermal comfort were undertaken on various types of buildings as an attempt to draw up that the interaction between the environment and the user is necessary to properly evaluate the indoor thermal comfort. The present research aims to explore the thermal quality within the French colonial houses in the town of Biskra where many passive techniques have been used for modifying the interior climate by promoting the passive cooling devices, inspired by the local traditional architecture. The courtyard, which is a one of the bioclimatic strategies to reduce the external climatic constraints, is also a key for passive cooling. Consequently, this work aims to characterize the impact of the patio in a saharan climate on the ambiance quality of the interior space of the houses. In this paper, an investigation is being conducted in five houses with patio, chosen as representative samples of colonial architecture in Biskra by an objective experimental method that contains in situ useful measurements for the calculation of Top and Tmr comfort indices according to the ISO 7730 standard for the evaluation of thermal comfort summer. In order to build more comfortable houses, many traditional techniques could be improved by using modern knowledge, rather than to be totally abandoned.